REDUCTION OF EMERGENCY DEPARTMENT VISIT USING AN URGENT CLINIC FOR ADULT WITH COPD - Fatima Obaid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease that causes obstruction of airflow out of the lungs. Symptoms include difficulty breathing, coughing, mucus (phlegm) build-up, and wheezing. It is usually caused by prolonged exposure to irritating gases or particles, often from cigarette smoke. People with COPD are at increased risk of heart disease, lung cancer, and a variety of other conditionsChronic bronchitis is an inflammation of the lining of the bronchial tubes that carry air to and from the air sacs (alveoli) of the lungs. This disease is characterized by daily coughing and mucus (sputum) formation.